2023
DOI: 10.18295/squmj.1.2022.011
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytoclastic Vasculitis

Abstract: Scrub typhus is a disease endemic to the Indian subcontinent caused by the obligate intracellular pleomorphic organism, Orientia tsutsugamushi. Scrub typhus among other acute febrile illnesses present with prodromal symptoms of fever, malaise, myalgia, anorexia followed by a distinct maculopapular rash, hepatosplenomegaly, and lymphadenopathy. In this case report, we present a patient who developed a rare cutaneous vasculitis secondary to infection with Orientia tsutsugamushi. After performing the Weil Felix t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…
We read with interest the recent report of Vasireddy A et al about 10 leukocytoclastic vasculitis (LV) associated with a Scrub typhus infection affecting a 28-11 year-old male, who presented with multiple, palpable purpuric eruptions mainly on the 12 lower extremities. 1 The routine laboratory determinations were unremarkable, and blood 13 confirmation of LV, 68.4% males, median age of 48.4 (13-93) years; 3 patients had 34 diagnosis of IgA vasculitis, 5 had diagnosis of urticarial vasculitis, and the 11 others 35 were considered as LV. Palpable purpura (with or without necrosis and hemorrhagic 36 blistering) was the predominant manifestation; and the commonest affected areas were 37 the lower limbs and the trunk.
…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…
We read with interest the recent report of Vasireddy A et al about 10 leukocytoclastic vasculitis (LV) associated with a Scrub typhus infection affecting a 28-11 year-old male, who presented with multiple, palpable purpuric eruptions mainly on the 12 lower extremities. 1 The routine laboratory determinations were unremarkable, and blood 13 confirmation of LV, 68.4% males, median age of 48.4 (13-93) years; 3 patients had 34 diagnosis of IgA vasculitis, 5 had diagnosis of urticarial vasculitis, and the 11 others 35 were considered as LV. Palpable purpura (with or without necrosis and hemorrhagic 36 blistering) was the predominant manifestation; and the commonest affected areas were 37 the lower limbs and the trunk.
…”
mentioning
confidence: 95%
“…about leukocytoclastic vasculitis (LV) associated with a Scrub typhus infection affecting a 28-year-old male, who presented with multiple, palpable purpuric eruptions mainly on the lower extremities. 1 The routine laboratory determinations were unremarkable and blood specific tests for autoimmune disorders, as well as malaria and bacterial and viral infections were negative; except for the Weil Felix test that was positive with a titre over 1:640 against OXK. Biopsy study of skin lesion showed the dermis with vasculo-centric infiltrate, and vessel walls with fibrinoid necrosis and dense infiltration by neutrophils, and leukocytoclasis.…”
mentioning
confidence: 95%
See 1 more Smart Citation